Multi-robot Search in a 3D Environment with Intersection System Constraints - Li, Yan-Shuo; Tseng, Kuo-Shih (2024 IEEE International Conference on Robotics and Automation (ICRA), 2024)
Efficient task allocation is a challenge for multirobot search. The multi-robot search problem is reformulated as submodular maximization subject to intersection system constraints. The objective function is submodular and consists of a coverage function to cover environments and a balancing function to efficiently dispatch robots. The intersection system is composed of routing and clustering constraints. The experiment results show that the proposed approach outperforms state-ofthe-art methods in multi-robot search.